Persistent Heterogeneities in the Oceanic Lithosphere Due To Differential Freezing Beneath Ridges - Shi Joyce Sim; Ting‐Ying Yu; Chris Havlin (Geophysical Research Letters)
Abstract Oceanic lithosphere, which forms two‐thirds of Earth's surface, is generated at mid‐ocean ridge spreading centers. Yet the internal structure of the lithosphere is not well characterized and often considered to be homogeneous relative to the structure of continental lithosphere. While geophysical observations clearly delineate the crust‐mantle boundary and the lithosphere‐asthenopshere boundary, other seismic anomalies known as mid‐lithosphere discontinuities (MLDs) have been challenging to detect and poorly constrained. Here we present melt transport models applied to the mid‐ocean ridge system that indicate MLDs are a widespread fundamental feature of oceanic lithosphere. In our models, some melt generated from decompression melting is frozen back into the lithosphere, forming a layered refertilization pattern. These refertilized layers are due to the stacked horizontal layering pattern of melt pooling beneath the freezing front. If the recrystallized melt is incorporated into the lithosphere as mafic lenses, the predicted seismic velocity is compatible with observations.